Psychological impacts of returning to laboral activities during the COVID-19 pandemic in a Regional Health Polyclinic in the State of Bahia, Brazil: an experience report (Research, Society and Development, 2020)
To describe the possible influences of returning to laboral activities during the COVID – 19 pandemic on the mental health of nursing professionals at a Regional Health Polyclinic located in the interior of Bahia. For that, we used the report of experience of qualitative approach and descriptive nature, whose locus of the action took place in a Polyclinic in Bahia in the face of the place of the work activities of one of the authors in against the pandemic, with the range of time from March to August 2020. The pandemic has led to an impact on the mental and physical health of health professionals, especially with regard to the continuous and exacerbated experience of negative emotions. Thus, the returning to work activities, the emotions that stood out were the excessive concern, the fear of being contaminated and of contaminating family members, insecurity due to the unexpected. In addition, the routine adopted by the unit and the dull use of Personal Protective Equipment (PPE) generated tiredness and physical exhaustion. So, as a way to relieve the fear, a drastic family routine was adopted, avoiding close contact with my family members. However, as time passed, these emotions were exchanged for the pleasure of attending and reinforced by the population acknowledgement, thus initiating the acceptance process. It is concluded that the fear of being contaminated and contaminating family members is the most expressed emotion during the return to work activities, followed by drastic changes in the daily and family routine. However, in the face of this “new normal”, the expansion of interdisciplinary methodologies in favor of health promotion by health professionals is relevant, including psychotherapy and group work.